Embracing the Sacred Trust: Said Nursi’s Sufism as a Pathway to Climate Resilience and Environmental Stewardship - Zein Muchamad Masykur; Nasrudin (Asian Journal of Philosophy and Religion, 2024)
This study explores the contributions of prominent Muslim scholar Said Nursi to addressing climate change. Through a qualitative analysis of his works, the research reveals Nursi's view of nature as a divine verse requiring respect and preservation. His emphasis on humans' responsibility as caliphs on Earth to maintain balance and harmony aligns with contemporary environmental concerns. Nursi's teachings on simplicity and moderation offer practical guidance for reducing human impact on the environment. The study concludes that Nursi's ethical and spiritual framework provides a holistic approach to climate change, offering a valuable perspective for developing more comprehensive and sustainable strategies.